ASSESSMENT OF THE 5th GRADE STUDENTS IN SCIENCE AND ART CENTERS WITH RESPECT TO THEIR NARRATIVE TEXT WRITING SKILLS - Ali YAYLACIK (Fırat University, 2019)
This is a descriptive study which aimed to identify narrative text writing levels of the gifted 5th graders at science and art centers (BİLSEM) and secondary school 5th graders in terms of text elements. The children who are superior to their peers with regard to various characteristics such as intelligence, creativity, art and leadership, and are described to give an outstanding performance by the experts. Today, education for the gifted students is provided by “Science and Art Centers”. The students are trained in the fields of adaptation, support education, the way to be aware of their skills and project production/management. The sample of the study which was conducted in a descriptive correlational survey model consisted of 145 gifted 5th graders studying at science and art centers in Gaziantep, Hatay and Kahramanmaraş and 140 5th graders studying at secondary schools in the same cities in 2013-2014 academic year. The most suitable three subjects out of ten were decided for children by teachers and domain experts. The students were asked to write a narrative text after choosing one of those three topics. “Story Elements Rating Scale” was applied for evaluating the stories written by the students. It was found out in the study that there was significant difference in the stories written by the gifted students and secondary school 5th graders in favor of the gifted students with respect to main character, setting, precipitating incident, aim, attempt and conclusion. Furthermore, statistically significant difference in favor of the girls was determined in mean scores of the girls and boys regarding use of narrative text elements.